Визначення коефіцієнта масовіддачі у рідинній фазі при абсорбції СО2 водою в капілярно-пористих пристроях - Світлик, Андрій Миколайович; Прохоров, Олександр Миколайович (My University, 2015)
Для процесу абсорбції діоксиду вуглецю водою в капілярно-пористих каналах розроблена теоретична модель визначення коефіцієнта масовіддачі. Експериментально встановлено, що коефіцієнт масовіддачі ßL, залежить від зміни тиску в системі, температури води і діаметра капілярного каналу. Коефіцієнт ßL пропорційно залежить від величини температури води і обернено пропорційно залежить від зміни тиску в системі і діаметра капіляра. The process of absorption of carbon dioxide with water in capillary- porous channels developed a theoretical model determining factor mass transfer. Experimentally that mass transfer coefficient ßL depends on changes in system pressure, water temperature and diameter of the capillary channel. Coefficient ßL proportional to the magnitude of water temperature and inversely proportional to the pressure changes in the system and the diameter of the capillary. Using multivariate experiment provides a linear regression equation. Analysis of the equation showed that the coefficient in the liquid phase mass transfer ßL factors affecting research in the following order: the system pressure P, the capillary diameter dK and the water temperature t °C. This paper shows the dependence of the liquid phase in mass transfer the growth temperature and pressure changes on the system.
Keywords: кафедра машин і апаратів харчових та фармацевтичних виробництв; процес абсорбції; капілярно-пористий канал; діоксид вуглецю; коефіцієнт масопередачі і масовіддачі; capillary-porous channel; carbon dioxide; mass transfer coefficient and mass transfer; process of absorption